Macroeconomic policy coordination in a competitive real exchange rate strategy for development - Martin Rapetti (University of Massachusetts, Department of Economics, 2011)
Recent research has documented a positive relationship between real exchange rate (RER) levels and economic growth. The literature has interpreted this correlation as causality running from RER levels to growth rates; i.e., higher, undervalued, more competitive RERs tend to favor growth. Little effort has been made, however, on the analysis of the policy instruments required to implement a successful competitive RER strategy. An exchange rate policy targeting a permanent change in the RER may run into difficulties: it is well documented that nominal and real exchange rate movements are correlated almost one for one in the short run but such co-movement slowly vanishes in the long run. Targeting instead a transitory RER undervaluation can have long-lasting effects on economic performance if RER competitiveness is stable and durable enough to provide incentives for tradable activities to expand. The ability to provide such an environment may be beyond the scope of exchange rate policy. This paper aims to shed light on the complementary policies that facilitate the success of an exchange rate policy that temporarily increases competitiveness. A formal model inspired by Ros and Skott (1998) is developed to analyze these issues. The main conclusion is that an exchange rate depreciation would more likely trigger an acceleration of growth if it is simultaneously implemented with domestic demand management policies that prevent non-tradables price inflation and wage management policies that coordinate wage increases with tradable productivity growth.
Keywords: O11; E61; 330